Age-based maintenance for a fleet of haul trucks. Issue 4 (8th October 2018) - Chaowasakoo, Patarawan; Seppälä, Heikki; Koivo, Heikki
Abstract : Purpose: The most costly part in an open-pit mine is the transportation of material out of the mine. The efficiency of the truck-and-shovel fleet plays a major role in cost control. The paper aims to discuss these issues. Design/methodology/approach: The truck dispatching simulation model with consideration of age-based maintenance is proposed. Findings: This paper underlines an impact of truck dispatching decisions and reveals remarkable differences in the total production under different approaches of operational availability. Additionally, the simulated results introduce an effective scheduled maintenance for different truck age levels. Originality/value: The approach is based on a case study taking into account the stochastic equipment behavior and environment in a real open-pit mine. This approach can be used more generally in situations in which truck fleets are used to transport material.